The Seven Deadly Sins omnibus. 2 - Suzuki, Nakaba, 1977- (Kodansha USA Publishing, LLC, 2021)
"The Grizzly Sin of Sloth, King, still lives! Unfortunately, King not only refuses to help Meliodas in finding the remaining Sins, but declares Ban as his mortal enemy for obtaining eternal life at the cost of the life of his sister, Elaine. The Sin's enter a fighting competition to win back Diane's fabled hammer. There, they meet the fearsome skilled Guila, along with a new faction of Holy Knights who promise disaster and devastation!"--Back cover.